Time; Literature; History. Some variations - Schnaiderman, Boris (Literatura e Sociedade, 2000)
This article inquires into the possibilities of applying the well-know difference between short duration (courte durée) and long duration (longue durée) - as it was posited by Fernand Braudel - to literary studies. It sketches some lines along which this appears in literature, philosophy and journalism. It also draws on some authors who help us to understand this issue.